Preparation method and application of full clay rod coating for dye / salt separation
The all-clay rod coating film prepared by ionic intercalation, liquid phase peeling and Meyer rod coating methods solves the problems of environmental pollution and high cost in the prior art, and achieves efficient and salt-resistant dye/salt separation performance. Significant application prospects.
Patent Information
- Application Number
- CN202310237888.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-13
AI Technical Summary
In the existing dye/salt separation technology, rod coatings prepared using organic polymers have problems such as environmental pollution, high cost, difficulty in expanding the preparation scale and poor salt resistance, and the application prospects of natural clay materials have not been fully utilized.
The natural clay material is used to prepare a large area, strong salt resistance, and full clay rod coating film through ionic intercalation, liquid phase peeling, ultrasonic mixing and Meyer rod coating. It is used for dye/salt separation, avoiding organic solvents and high costs. Use of materials.
It achieves efficient dye removal rate and salt resistance, reduces production costs, and is simple and easy to scale, providing a green and environmentally friendly dye/salt separation solution.
Smart Images

Figure CN116212660B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dye / salt membrane separation, and more specifically, relates to a method for preparing a full-clay rod coating for dye / salt separation and an application thereof. Background Art
[0002] With the development of domestic textile industry and other industries, the printing and dyeing wastewater produced has become one of the main causes of water pollution due to its toxicity, high salinity and chromaticity. Traditional chemical oxidation, absorption, flocculation and other processes often have low separation efficiency, waste resources, and even the addition of new chemicals during the treatment process will cause secondary pollution. In order to better solve this serious problem, it is necessary to efficiently separate high value-added materials (i.e. dyes and salts) in addition to removing pollutants. Membrane separation technology is suitable for the field of dye desalination due to its low energy consumption, high recovery rate and no negative impact on the environment.
[0003] Most water-soluble dyes have a molecular weight less than 2000Da. In membrane separation technology, the molecular weight cutoff (MWCO) of nanofiltration membranes is 200-1000Da. The membrane can efficiently intercept dye molecules through the steric effect of the membrane. At the same time, the interception rate for monovalent salt ions is low, making it one of the best choices for dye desalination membranes.
[0004] In view of the excellent performance of nanofiltration membranes, many domestic patents have been applied to the field of dye desalination. Gao Congqi's research group at Zhejiang University of Technology used the pressurized sedimentation filtration-chemical cross-linking method to prepare a triazine-based porous organic nanoparticle assembly membrane in the "Preparation Method of Triazine-Based Porous Organic Nanoparticle Assembly Membrane" (CN111921383A). The Congo red dye interception rate can reach 98%, the inorganic salt interception rate is less than 10%, and the interception flux can reach 75L m -2 h -1 bar -1 ; Chen Yingbo's research group at Tianjin Polytechnic University used an online coating device to prepare a high-strength double-layer hollow organic composite nanofiltration membrane with a separation pore size by phase inversion in the "Preparation method of a double-layer hollow fiber loose nanofiltration membrane for dye desalination" (CN113769586 A). The methylene blue retention rate was 98.86%, the NaCl retention rate was 3.2%, and the retention flux was 14.2 L m -2 h -1 bar -1; In the study “A method for preparing graphene oxide / modified titanium dioxide composite nanofiltration membrane by multi-effect coupling and its application in dye desalination” (CN 110772993 A), Shen Jiangnan’s research group at Zhejiang University of Technology used vacuum filtration to prepare GO / nano-TiO2 / dopamine composite membrane, which had a dye retention rate of 99.8% and a sodium sulfate retention of 3.2%, and had good salt resistance. In the study “A calcium alginate hydrogel filtration membrane containing black phosphorus / graphene oxide and its preparation method”, Zhao Kongyin’s research group at Nanjing University of Technology obtained a calcium alginate hydrogel filtration membrane containing black phosphorus / graphene oxide by blade coating-ionic crosslinking. The membrane is environmentally friendly, has good dye-salt separation performance, and has good application prospects. Professor Wang Baodui of Lanzhou University used the property of polymer functional groups to form coordination bonds and hydrogen bonds with attapulgite metal ions and hydroxyl groups, and controlled the pore size of the nanofiltration membrane by controlling the proportion of polymer in the composite nanofiltration membrane. He used vacuum-assisted filtration or rod coating room temperature evaporation as the driving force to prepare a nanofiltration membrane with a multilayer structure through self-assembly. The composite nanofiltration membrane has a certain separation effect on dyes / salts, with a retention flux of 25L m -2 h -1 bar -1 The clay-organic composite membrane developed by Ma Yuxin's research group at Harbin Institute of Technology in the project "A polyvinylidene fluoride / organic clay nanocomposite ultra-low pressure ultrafiltration membrane and its preparation method" can achieve high processing flux at less than 0.05MPa and has a certain dye / salt separation ability.
[0005] However, most of the existing rod coating technologies use organic polymers or their composite membranes. The production and use of organic solvents is not environmentally friendly and can easily cause other pollution. Some nanomaterials are mostly prepared using small-scale methods such as vacuum filtration. The preparation scale is difficult to expand, and the use of nanomaterials is expensive and not suitable for industrial production. Although green biomass composite membranes (such as sodium alginate) can be prepared on a large scale using rod coating and other methods, their dye desalination performance has not been tested in actual applications, and their salt resistance and antibacterial properties are poor. Natural clay is a green, abundant, and inexpensive nanomaterial. One-dimensional nanoclay materials (attapulgite, sepiolite, halloysite), two-dimensional nanoclay materials (kaolinite, vermiculite, montmorillonite), etc. are natural nanoscale hydrous magnesium-aluminum silicate clay minerals, all of which have regular crystal structures and nanopores. These clay minerals have a large number of hydroxyl groups and reactive groups on their surfaces, which make them highly hydrophilic and chemically reactive. However, the clay nanofiltration membrane used for dye / salt separation in the current invention patent needs to be combined with organic polymers to ensure its excellent separation performance. The addition of organic polymers not only greatly increases the cost, but also easily pollutes the green and environmentally friendly clay materials.
[0006] Therefore, this patent proposes a method for preparing and applying a full clay rod coating for dye / salt separation, using the abundant and inexpensive clay for liquid phase exfoliation to obtain a nano-dispersion, and using Meyer rod coating to obtain a full clay rod coating with a large area, high dye / salt separation performance, and good salt resistance. Summary of the invention
[0007] The purpose of the present invention is to propose a preparation method and application of a full clay rod coating for dye / salt separation in view of the defects of the prior art. The full clay rod coating of the present invention has a stable structure, high interception flux, high dye removal rate, and excellent salt resistance. The preparation method thereof has low production cost, simple preparation process, and easy expansion of preparation scale; the clay rod coating material of the present invention has excellent application prospects in the field of dye / salt separation.
[0008] The technical solution adopted by the present invention to solve the problems of the prior art is as follows:
[0009] A method for preparing a full clay rod coating for dye / salt separation, characterized in that the clay rod coating material is a large-area rod coating obtained by sequentially undergoing ion intercalation, liquid phase stripping, centrifugal concentration, ultrasonic mixing, and Mayer rod coating with natural clay as the material: the rod coating can achieve a dye removal rate of up to 99% in dye / salt separation, and the clay rod coating can continuously perform water treatment for a long time, and maintains structural integrity and stable properties after being immersed in water or strong acid (pH=1) or strong alkali solution (pH=14) for one week.
[0010] A method for preparing a full clay rod coating for dye / salt separation comprises the following steps:
[0011] S1. Hydrothermal reaction for ion intercalation of two-dimensional clay materials
[0012] The two-dimensional clay material and a saturated NaCl solution are mixed at a mass volume ratio of 3 mg / mL to 12 mg / mL, and then placed in a hydrothermal reactor, and heated at 100 to 120° C. for 1 to 3 hours to allow the mixture of the two-dimensional clay material and the saturated NaCl solution to undergo a hydrothermal reaction; when the hydrothermal reactor is cooled to room temperature, the solid product after the hydrothermal reaction is separated to obtain a primary solid product, and the primary solid product is washed with deionized water to obtain a washed solid product; the washed solid product is mixed with 100 mL of LiCl solution and then placed in a hydrothermal reactor again, and heated at 100 to 120° C. for 2 hours. When the hydrothermal reactor is cooled to room temperature, the solid product after the hydrothermal reaction is separated again to obtain a secondary treated solid product, and the secondary treated solid product is washed with deionized water to obtain a two-dimensional clay after ion intercalation; the concentration of the LiCl solution is 2 mol / L.
[0013] S2, liquid phase exfoliation assisted by high-speed shear
[0014] The two-dimensional clay after ion intercalation obtained in step S1 is mixed with deionized water at a mass volume ratio of 3.75 mg / mL to 15 mg / mL to form an ion intercalated clay mixed solution; the ion intercalated clay mixed solution is placed in a high-speed shear emulsifier, and stirred and peeled at a speed of 15000 to 25000 rpm in the high-speed shear emulsifier for 5 to 15 minutes to form a mixture containing clay nanosheets; and the mixture is centrifuged in a high-speed centrifuge at a speed of 300 rpm for 1 hour to remove incompletely peeled particles and impurities to obtain a clay nanosheet dispersion A;
[0015] S3, Ultrasonic Assisted Liquid Phase Exfoliation
[0016] The one-dimensional clay material and deionized water are mixed at a mass volume ratio of 30 mg / mL to form a mixed solution, and the one-dimensional clay mixed solution is ultrasonicated for 30-60 minutes with a 6-10 mm diameter probe to form a mixture containing clay nanofibers. The mixture is then centrifuged at 2000 rpm for 10 minutes in a high-speed centrifuge to remove incompletely peeled particles and impurities, thereby obtaining a high-concentration clay nanofiber dispersion B;
[0017] S4, centrifugal screening
[0018] The clay nanosheet dispersion obtained in step S2 is centrifuged and concentrated in a high-speed centrifuge at a speed of 6000 to 10000 rpm for 20 to 60 minutes to obtain a clay nanosheet concentrate, and after removing the supernatant of the clay nanosheet concentrate, the precipitate of the clay nanosheet concentrate is ultrasonically dispersed to obtain a high-concentration clay nanosheet dispersion B;
[0019] S5. Dispersion mixing
[0020] The two dispersions obtained in step S3 and step S4 were mixed at different volume ratios and subjected to bath ultrasonication for 10 min to ensure uniform mixing.
[0021] S6, composite film rod coating
[0022] The mixed dispersion in step S5 is coated on the polyethersulfone membrane substrate by a Meyer rod, and the coating speed of the Meyer rod is 20-40 mm s -1 , and dry for 30 minutes to obtain a large-area rod coating.
[0023] The two-dimensional clay material is one of vermiculite, montmorillonite and illite or a mixture of two or more thereof, and the one-dimensional clay material is sepiolite and / or palygorskite.
[0024] The method for separating the solid product in the hydrothermal reaction in step S1 includes suction filtration separation or centrifugal separation.
[0025] In step S3, the high concentration clay nanofiber dispersion A is diluted to a concentration of 15-25 mg / mL.
[0026] In step S4, the concentration of the high-concentration clay nanosheet dispersion B is concentrated to 15-25 mg / mL, which is consistent with the concentration of the high-concentration clay nanofiber dispersion A after dilution in step S3, and the volume ratio of the two is 2:8-8:2.
[0027] In step S6, the width of the groove of the Meyer bar is 4 to 10 mm.
[0028] The clay coating film is placed in a positive pressure filtration / vacuum filtration device for filtering dye wastewater, the dye concentration in the dye wastewater is 10-20 mg / mL, the concentration of the salt solution is 1-10 g / L. The dyes are methylene blue, Congo red, malachite green, and the salt solution is NaCl, Na2SO4, MgCl2, CaCl2.
[0029] The advantages and beneficial effects of the present invention over the prior art are as follows: the present invention uses clay particles with nano-layered structure and clay with nano-fibrous structure as raw materials, obtains two-dimensional clay nanosheets through ion intercalation assisted liquid phase exfoliation, and obtains large-area, strong salt resistance, high interception flux, and high dye removal rate clay rod coating film for dye / salt separation by ultrasonic assisted liquid phase exfoliation combined with rod coating. Because natural clay particles are abundant in reserves, cheap and easy to obtain, and environmentally friendly, they are more economical than nanomaterials such as graphene, MXene, and carbon nanotubes. For the stripping method of clay nanosheets and fibers, the present invention adopts a liquid phase exfoliation method, which has high production efficiency, mild reaction conditions, green environmental protection, and easy to expand the scale of reaction. In terms of preparation methods, no organic solvents, initiators, and surfactants are used in the preparation process of the two-dimensional nanosheet composite material, which has the advantages of being environmentally friendly, safe and easy to operate. The rod coating nano-dispersion liquid film-making method used in the present invention can quickly and large-scale prepare thin films for dye / salt separation, and the operation is safe and simple. The present invention explores that the appropriate mass ratio of one-dimensional and two-dimensional clay should be 2:8-8:2, so that the preparation method is simple to form a film and the prepared film has high treatment efficiency. The large-area full clay rod coating proposed by the present invention has significant application effects in the field of water treatment, especially dye / salt separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The long-term dye / salt separation performance test of the rod coating prepared in Example 1 was performed using a dye / salt mixed solution with a methylene blue concentration of 10 mg L -1 , sodium chloride concentration is 1 g L -1 . DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with specific embodiments, but is not limited to the following embodiments.
[0032] The two-dimensional clay material in the embodiment of the present invention can be one or more of vermiculite, montmorillonite, kaolin, and illite, preferably vermiculite as an example, but not limited thereto. The one-dimensional clay material can be sepiolite or palygorskite, but not limited thereto.
[0033] Embodiment 1:
[0034] A preparation method and application of a full clay rod coating for dye / salt separation, comprising the following steps:
[0035] S1. Hydrothermal reaction for ion intercalation of two-dimensional clay materials
[0036] The two-dimensional clay material and the saturated NaCl solution are mixed at a mass volume ratio of 12 mg / mL, and then placed in a hydrothermal reactor, and heated at 110°C for 2 hours to allow the mixture of the two-dimensional clay material and the saturated NaCl solution to undergo a hydrothermal reaction; when the hydrothermal reactor is cooled to room temperature, the solid product after the hydrothermal reaction is separated to obtain a primary solid product, and the primary solid product is washed with deionized water to obtain a washed primary solid product; the washed primary solid product is mixed with a LiCl solution at a mass volume ratio of 12 mg / mL, and then placed in a hydrothermal reactor again, and heated at 110°C for 2 hours. When the hydrothermal reactor is cooled to room temperature, the solid product after the hydrothermal reaction is separated again to obtain a secondary solid product, and the secondary solid product is washed with deionized water to obtain a two-dimensional clay after ion intercalation; the concentration of the LiCl solution is 2 mol / L.
[0037] S2, liquid phase exfoliation assisted by high-speed shear
[0038] The two-dimensional clay after ion intercalation obtained in step S1 is mixed with 80 mL of deionized water to form a clay mixture after ion intercalation. The clay mixture after ion intercalation is placed in a high-speed shear emulsifier, and stirred and peeled at a speed of 20,000 rpm in the high-speed shear emulsifier for 10 minutes to form a mixture containing clay nanosheets; then the mixture is centrifuged in a high-speed centrifuge at a speed of 300 rpm for 1 hour to remove incompletely peeled particles and impurities, and obtain a clay nanosheet dispersion;
[0039] S3, Ultrasonic Assisted Liquid Phase Exfoliation
[0040] The one-dimensional clay material and deionized water were mixed at a mass volume ratio of 30 mg / mL to form a mixed solution, and the one-dimensional clay mixed solution was ultrasonicated for 30 minutes using a 10 cm diameter probe tip to form a mixture containing clay nanofibers. The mixture was then centrifuged in a high-speed centrifuge at a speed of 2000 rpm for 10 minutes to remove incompletely peeled particles and impurities, thereby obtaining a high-concentration clay nanofiber dispersion A;
[0041] S4, centrifugal screening
[0042] The clay nanosheet dispersion obtained in step S2 is centrifuged and concentrated in a high-speed centrifuge at a speed of 6000 rpm for 60 minutes to obtain a clay nanosheet concentrate, and after removing the supernatant of the clay nanosheet concentrate, the precipitate of the clay nanosheet concentrate is ultrasonically dispersed to obtain a high-concentration clay nanosheet dispersion B;
[0043] S5. Dispersion mixing
[0044] The two dispersions obtained in step S3 and step S4 were diluted and concentrated to 20 mg / mL, mixed at a volume ratio of 4:1, and subjected to bath ultrasound for 10 min to ensure uniform mixing.
[0045] S6, composite film rod coating
[0046] The mixed dispersion in step S5 was coated on the polyethersulfone membrane substrate by a Meyer rod (the coating speed of the Meyer rod was 25 mms -1 ), and dry for 30 minutes to obtain a large-area rod coating (20mm*30mm).
[0047] Application of the clay bar coating obtained in Example 1:
[0048] Application Example 1: The clay rod coating obtained in Example 1 was placed in a positive pressure filtration device, and a mixed solution with a methylene blue concentration of 10 mg / L and a sodium chloride concentration of 1 g / L was added to the device for positive pressure filtration. The methylene blue removal rate can reach 97.65%, the sodium chloride retention rate is only 6.28%, and the retention flux is 72.53 L m -2 bar -1 h -1 , dye / salt separation was well achieved.
[0049] Application Example 2: The other application conditions in Application Example 2 are the same as those in Application Example 1. Only the concentration of sodium chloride in the solution is changed to 10 g / L. The removal rate of methylene blue can reach 97.65%, the retention rate of sodium chloride is only 5.02%, and the retention flux is 67.14 L m - 2 bar -1 h -1 , dye / salt separation was well achieved.
[0050] Application Example 3: The other application conditions in Application Example 2 are the same as those in Application Example 1. Only 10 mg / L methylene blue in the mixed solution is replaced with 10 mg / L Congo red. The Congo red removal rate can reach 98.12%, the sodium chloride retention rate is only 6.32%, and the retention flux is 66.28 L m -2 bar -1 h -1 , dye / salt separation was well achieved.
[0051] Application Example 4: The other application conditions in Application Example 2 are the same as those in Application Example 1. Only 1g / L sodium chloride in the mixed solution is replaced with 1g / L sodium sulfate. The removal rate of methylene blue can reach 97.97%, the retention rate of sodium sulfate is only 6.51%, and the retention flux is 65.38Lm -2 bar -1 h -1 , dye / salt separation was well achieved.
[0052] Application Example 5: The clay rod coating obtained in Example 1 was placed in a positive pressure filtration device, and a mixed solution with a methylene blue concentration of 10 mg / L and a sodium sulfate concentration of 1 g / L was added to the device for long-term continuous (24 h) positive pressure filtration. Figure 1 The methylene blue removal rate can be maintained above 95%, the sodium chloride retention rate is only maintained at 7%-10%, and the retention flux is maintained at 75-80 L m -2 bar -1 h -1 , dye / salt separation was well achieved.
[0053] Embodiment 2:
[0054] The preparation steps of Example 2 are the same as those of Example 1 except that the dispersion volume ratio of S5 is changed to 3:2.
[0055] Application of the clay bar coating obtained in Example 2:
[0056] The clay rod coating obtained in Example 2 was placed in a positive pressure filtration device, and a mixed solution with a methylene blue concentration of 10 mg / L and a sodium chloride concentration of 1 g / L was added to the device for positive pressure filtration. The methylene blue removal rate could reach 98.15%, the sodium chloride retention rate was only 6.02%, and the retention flux was 64.53 L m -2 bar -1 h -1 , dye / salt separation was well achieved.
[0057] Embodiment 3:
[0058] The preparation steps of Example 3 are the same as those of Example 1 except that the volume ratio of the dispersion of S5 is changed to 2:3.
[0059] Application of the clay bar coating obtained in Example 3:
[0060] The clay rod coating obtained in Example 3 was placed in a positive pressure filtration device, and a mixed solution with a methylene blue concentration of 10 mg / L and a sodium chloride concentration of 1 g / L was added to the device for positive pressure filtration. The methylene blue removal rate could reach 98.62%, the sodium chloride retention rate was only 9.25%, and the retention flux was 28.58 L m -2 bar -1 h -1 , dye / salt separation was well achieved.
[0061] Embodiment 4:
[0062] The preparation steps of Example 4 are the same as those of Example 1 except that the dispersion volume ratio of S5 is changed to 1:4. The remaining preparation steps are the same as those of Example 1.
[0063] Application of the clay bar coating obtained in Example 4:
[0064] The clay rod coating obtained in Example 4 was placed in a positive pressure filtration device, and a mixed solution with a methylene blue concentration of 10 mg / L and a sodium chloride concentration of 1 g / L was added to the device for positive pressure filtration. The methylene blue removal rate could reach 99.11%, the sodium chloride retention rate was only 12.97%, and the retention flux was 23.37 L m -2 bar -1 h -1 , dye / salt separation was well achieved.
[0065] Example 5
[0066] In the preparation steps of Example 5, only the concentration of the two dispersions (dispersion A and B) in S5 was controlled to 25 mg / mL, and the rest of the preparation steps were the same as those of Example 1. The preparation method of Example 5 can be used to form a membrane by rod coating, and the interception flux and dye / salt separation capacity are close to those of Example 1.
[0067] Example 6
[0068] In the preparation steps of Example 6, only the concentration of the two dispersions (dispersion A and B) in S5 was controlled to 15 mg / mL, and the rest of the preparation steps were the same as those of Example 1. The preparation method of Example 6 can be used to form a membrane by rod coating, and the interception flux and dye / salt separation capacity are close to those of Example 1.
[0069] Comparative Example 1:
[0070] In the preparation steps of Comparative Example 1, only the dispersion volume ratio of Example 1S5 is changed to 1:9, and the rest of the preparation steps are the same as Example 1. According to the preparation method of Comparative Example 1, it is impossible to form a film by rod coating, that is, the volume proportion of the sepiolite nanofiber dispersion cannot exceed 80%, otherwise there are too few nanosheets and too many nanosheet fibers, and no film can be formed.
[0071] Comparative Example 2:
[0072] In the preparation steps of Comparative Example 2, only the volume ratio of the two dispersions in S5 was changed to 9:1, and the rest of the preparation steps were the same as those in Example 1. The rod coating method of Comparative Example 2 can form a membrane, but the interception flux is reduced to 10 L m -2 bar -1 h -1 , cannot meet the requirements of efficient dye / salt separation.
[0073] Comparative Example 3
[0074] In the preparation steps of Comparative Example 3, only the concentration of the two dispersions (dispersion A and B) in S5 was controlled to 30 mg / mL, and the remaining preparation steps were the same as those in Example 1. However, according to the preparation conditions of Comparative Example 3, rod coating to form a film was not possible.
[0075] Comparative Example 4
[0076] In the preparation steps of Comparative Example 4, only the concentration of the two dispersions (dispersion A and B) in S5 was controlled to 10 mg / mL, and the remaining preparation steps were the same as those in Example 1. However, according to the preparation conditions of Comparative Example 4, rod coating to form a film was not possible.
[0077] In summary, in the preparation of a full clay rod coating for dye / salt separation, the mass proportion of one-dimensional and two-dimensional clay in the composite membrane and the concentration of the clay mixed dispersion are important factors affecting the film forming properties and membrane performance.
[0078] The above contents are further detailed descriptions of the present invention in combination with specific preferred technical solutions, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a full clay scraping film for dye / salt separation, characterized in that: The following steps are involved: S1. Hydrothermal reaction for ion intercalation of two-dimensional clay materials The two-dimensional clay material and the saturated NaCl solution are mixed at a mass volume ratio of 3 mg / mL-12 mg / mL, and then placed in a hydrothermal reactor, and heated at 100-120°C for 1-3 hours to allow the mixture of the two-dimensional clay material and the saturated NaCl solution to undergo a hydrothermal reaction; when the hydrothermal reactor is cooled to room temperature, the solid product after the hydrothermal reaction is separated to obtain a primary solid product, and the primary solid product is washed with deionized water to obtain a washed solid product; the washed solid product is mixed with a LiCl solution at a mass volume ratio of 3 mg / mL-12 mg / mL, and then placed in a hydrothermal reactor again, and heated at 100-120°C for 2 hours. When the hydrothermal reactor is cooled to room temperature, the solid product after the hydrothermal reaction is separated again to obtain a secondary treated solid product, and the secondary treated solid product is washed with deionized water to obtain a two-dimensional clay after ion intercalation; the concentration of the LiCl solution is 2 mol / L; S2, liquid phase exfoliation assisted by high-speed shear The two-dimensional clay after ion intercalation obtained in step S1 is mixed with deionized water at a mass volume ratio of 3.75 mg / mL to 15 mg / mL to form an ion intercalated clay mixed solution; the ion intercalated clay mixed solution is placed in a high-speed shear emulsifier, and stirred and peeled at a speed of 15000 to 25000 rpm in the high-speed shear emulsifier for 5 to 15 minutes to form a mixture containing clay nanosheets; and the mixture is centrifuged in a high-speed centrifuge at a speed of 300 rpm for 1 hour to remove incompletely peeled particles and impurities to obtain a clay nanosheet dispersion; S3, Ultrasonic Assisted Liquid Phase Exfoliation A one-dimensional clay material and deionized water are mixed at a rate of 30 mg / mL to form a one-dimensional clay mixed solution, and the one-dimensional clay mixed solution is then ultrasonicated for 30-60 minutes using a 6-10 mm diameter probe to form a mixture containing clay nanofibers; the mixture is then centrifuged at 2000 rpm in a high-speed centrifuge for 10 minutes to remove incompletely peeled particles and impurities, to obtain a high-concentration clay nanofiber dispersion A; S4, centrifugal screening The clay nanosheet dispersion obtained in step S2 is centrifuged and concentrated in a high-speed centrifuge at a speed of 6000 to 10000 rpm for 20 to 60 minutes to obtain a clay nanosheet concentrate, and after removing the supernatant of the clay nanosheet concentrate, the precipitate of the clay nanosheet concentrate is ultrasonically dispersed to obtain a high-concentration clay nanosheet dispersion B; S5. Dispersion mixing The two dispersions obtained in step S3 and S4 are diluted and concentrated, mixed at a volume ratio of 2:8-8:2, and subjected to bath ultrasonication for 10 minutes to ensure uniform mixing; The high concentration clay nanofiber dispersion A obtained in step S3 is diluted to a concentration of 15-25 mg / mL; the high concentration clay nanosheet dispersion B obtained in step S4 is concentrated to a concentration of 15-25 mg / mL, which is consistent with the concentration of the high concentration clay nanofiber dispersion A after dilution in step S3; S6, composite film coating The mixed dispersion in step S5 is coated on the polyethersulfone membrane substrate by a Meyer rod, and the coating speed of the Meyer rod is 20-40 mms -1 , dry for 30 minutes to obtain a large area of clay scraping film; In step S6, the width of the groove of the Meyer bar is 4 to 10 mm.
2. The preparation method according to claim 1, characterized in that: The two-dimensional clay material is one of vermiculite, montmorillonite and illite or a mixture of two or more thereof, and the one-dimensional clay material is sepiolite and / or palygorskite.
3. The preparation method according to claim 1 or 2, characterized in that: The method for separating the solid product in the hydrothermal reaction in step S1 includes suction filtration separation or centrifugal separation.
4. The preparation method according to claim 1, characterized in that: The clay coating film is placed in a positive pressure filtration / vacuum filtration device to filter dye wastewater, in which the dye concentration is 10-20 mg / mL and the concentration of the salt solution is 1-10 g / L.
5. The preparation method according to claim 4, characterized in that: The dyes are methylene blue, Congo red, and malachite green, and the salt solutions are NaCl, Na2SO4, MgCl2, and CaCl2.